Microstructure and Hydrogen Embrittlement Sensitivity of 38CrMoAlNitriding Steel Treated by Vacuum Carburizing - ZHAO Hua-rui, DING Yan-xia (Cailiao Baohu, 2021)
In order to meet the requirements of material properties for automotive lightweight, 38CrMoAl nitriding steel for gear was selected as the test material. The hydrogen embrittlement sensitivity of vacuum carburizing (VC) samples was tested by electrochemical hydrogen charging method combined with slow strain tensile, which was compared with quenching and low tempering (QL) treated samples. Results showed that the uniform form of low carbon tempered martensite was formed in the QL sample. Carburized layer of VC sample was dominated by high carbon tempered martensite, and there was a small amount of residual austenite.VC sample reached the maximum hardness of 732 HV on the surface while QL sample was near 450 HV. After hydrogen charging, the tensile strength of the QL sample was close to that of the original sample while the elongation after fracture(HEI) was significantly reduced. Calculating the difference of relative elongation after fracture indicated that the hydrogen embrittlement sensitivity index (HEI) of QL sample was 54.3%. The hydrogen embrittlement sensitivity of 38CrMoAl nitriding steel was increased rapidly after carburizing treatment. After hydrogen charging treatment, QL sample had more obvious brittle fracture, which was similar to the hydrogen induced fracture of high strength martensitic steel. VC samples treated with hydrogen charging formed many dimple-like structures after fracture, showing the characteristics of ductile fracture.